2019
DOI: 10.1051/0004-6361/201834191
|View full text |Cite
|
Sign up to set email alerts
|

Model for Population III microquasars

Abstract: Context. Current simulations indicate that the first stars were formed predominantly in binary systems. Studying the contribution of the first accreting binary systems to the reionization and heating of the intergalactic medium requires formulating a concrete model for Population III microquasars. Aims. We aim at constructing a complete model for microquasars with a Population III donor star. Methods. We considered that the mass loss of the star is exclusively caused by the spill of matter through the Roche lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
0
14
0
1
Order By: Relevance
“…We have applied our study to PopIII MQs. In order to model the jet-wind interaction in these objects we have adopted the model developed by Sotomayor Checa and Romero (2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have applied our study to PopIII MQs. In order to model the jet-wind interaction in these objects we have adopted the model developed by Sotomayor Checa and Romero (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The wind provides an additional source of ultraviolet radiation and soft X-rays. Sotomayor Checa and Romero (2019) showed that in the context of Population III microquasars, the emission from disk wind may be higher than the blackbody emission from the disk.…”
Section: Super-critical Accretion Disks and Their Windsmentioning
confidence: 99%
See 2 more Smart Citations
“…All calculations have been computed for a cosmological redshift value z = 10. Preliminary results have been presented in Romero & Sotomayor Checa (2018) and Sotomayor Checa & Romero (2019).…”
Section: Introductionmentioning
confidence: 99%